2019
DOI: 10.5603/gp.2019.0024
|View full text |Cite
|
Sign up to set email alerts
|

The potential predictive value of serum srCaS1 levels for overall survival in endometrial cancer

Abstract: Objectives:The main aim of the study was to evaluate the impact of levels of serum soluble receptor-binding cancer antigen expressed on SiSo cells (sRCAS1) on the overall survival (OS) rates in patients with endometrial cancer. Furthermore, we analyzed sRCAS1 levels according to the clinicopathological characteristics of the disease. Material and methods:The study group comprised 43 patients who were being treated for endometrial cancer. We included 10 low-risk, 20 intermediate-risk and 13 high-risk endometria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In contrast, the pre‐treatment sRCAS1 and the alteration in sRCAS1 levels before and after the treatment were not related to the long‐term outcome for the patient. We had achieved similar results in our previous study that was focused on serum sRCAS1 levels in patients with endometrial cancer, where we found that post‐surgery serum sRCAS1 alone was associated with patient survival . Because of the strong immunosuppressive effect of the RCAS1, our results suggest that the intensity of the selective suppression of the host's immune system at the end of the primary treatment exerts the observed impact on the patient prognosis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the pre‐treatment sRCAS1 and the alteration in sRCAS1 levels before and after the treatment were not related to the long‐term outcome for the patient. We had achieved similar results in our previous study that was focused on serum sRCAS1 levels in patients with endometrial cancer, where we found that post‐surgery serum sRCAS1 alone was associated with patient survival . Because of the strong immunosuppressive effect of the RCAS1, our results suggest that the intensity of the selective suppression of the host's immune system at the end of the primary treatment exerts the observed impact on the patient prognosis.…”
Section: Discussionsupporting
confidence: 84%
“…We had achieved similar results in our previous study that was focused on serum sRCAS1 levels in patients with endometrial cancer, where we found that post-surgery serum sRCAS1 alone was associated with patient survival. 28 Because of the strong immunosuppressive effect of the RCAS1, our results suggest that the intensity of the selective suppression of the host's immune system at the end of the primary treatment exerts the observed impact on the patient prognosis. On the other hand, pretreatment serum sRCAS1 levels may correlate with cancer incidence, and serum sRCAS1 levels were found to be higher in several of the study group neoplasms compared with levels on the healthy controls.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, RCAS1 expression and metastasis were clinically significant predictors of OS according to multivariate analysis (72). Recently, Szubert et al (73) suggested that high levels of RCAS1 in post-surgery serum are an independent p redictor of shortened OS time in patients with EC.…”
Section: Receptor-binding Cancer Antigen Expressed On Siso Cells (Rcas1)mentioning
confidence: 99%